The Effect of Contextual Learning Trough Teaching Materials Application-Based on Problem Solving Ability - Ismi Zakiah; Heris Hendriana; Wahyu Hidayat (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2022)
Explanation of material is still in the form of calculations and teaching materials used are in the form of teaching modules that are not based on contextual problems. This is difficult to apply in bold learning, so students still have difficulty solving problems. This study aims to measure the effectiveness of contextual learning using application-based teaching materials on students' problem solving abilities. This research method uses true experimental, while the research design used is a randomized posttest only control group. The subjects in this study were class VII A and VII B with a total of 64 students. The data collection in this research uses quantitative data and the instrument used is a mathematical problem solving ability test. Data analysis in this study was using one-sample t-test and independent t-test. The results of the calculation that students have achieved the minimum criteria completeness score that is more than 70, this can be seen in the results of the one-sample t-test which obtained a sig value of 0.008 and students who used contextual learning with application-based teaching materials were better than contextual learning. This can be seen in the independent t-test, which obtained a value of sig .000, meaning that the value of sig < 0.05. So that contextual learning uses application-based teaching materials for problem solving that is effectively applied in learning mathematics